2005
DOI: 10.1021/es040454m
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Organochlorine Pesticides from Water Using Triolein Embedded Cellulose Acetate Membranes

Abstract: A new type of composite membrane, triolein embedded cellulose acetate membrane (TECAM), was produced by embedding triolein drops in the matrix of cellulose acetate polymers. The distribution of six organochlorine pesticides (OCPs) between water and TECAM was investigated in a static water system. Its field application was tested in Taihu Lake (China). Results from both laboratory and field experiments indicate that TECAM quickly and efficiently accumulated hydrophobic OCPs from water. Under laboratory conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 24 publications
4
62
0
Order By: Relevance
“…In the case of the SPMD, the approach of a curve region could be observed for naphthalene and phenanthrene at the end of exposure, but for benzo [b]fluoranthene and benzo[a]pyrene, the uptake remained in the linear uptake phase similar to that observed for TECAMs. This is not surprising because in our earlier study for target compounds with similar hydrophobicity shorter equilibrium times were also observed for TECAMs compared to SPMDs (11).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…In the case of the SPMD, the approach of a curve region could be observed for naphthalene and phenanthrene at the end of exposure, but for benzo [b]fluoranthene and benzo[a]pyrene, the uptake remained in the linear uptake phase similar to that observed for TECAMs. This is not surprising because in our earlier study for target compounds with similar hydrophobicity shorter equilibrium times were also observed for TECAMs compared to SPMDs (11).…”
Section: Resultssupporting
confidence: 69%
“…The TECAMs were prepared in a clean room to reduce vapor-phase contamination. Details of the preparation of TECAMs were reported elsewhere (11). TECAMs were constructed in the same configuration: 40-50 µm thick, 12 cm wide, and 18 cm long.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvent and other chemicals used in the study were of GC or analytical reagent grade. Small pieces of TECAM (4 cm  6 cm) were used and the procedure for preparing was the same as described previously [22].…”
Section: Reagents and Chemicalsmentioning
confidence: 99%
“…Compared with normal adsorbents such as activated carbon and alumina, this DNA matrix showed a selective adsorptivity for the dioxin derivatives with planar structure such as dibenzo-p-dioxin, dibenzofuran, and biphenyl. Some researchers (Xu et al, 2005b;Ke et al, 2006) prepared a new type of composite membrane, triolein embedded-cellulose acetate membrane (TECAM), and used it in the uptake of six organochlorine pesticides. Results indicated that TECAM quickly and efficiently accumulated hydrophobic organochlorine pesticides (OCPs) from water.…”
Section: Biomimetic Sorbent and Its Sorption Behaviors Of Persistent mentioning
confidence: 99%